Effect of Working Environment on Employees Performance in Mbale City - Enock Musika (Uganda Christian University, 2024)
Improved performance is accomplished through the employees of the organization. Employees are not viewed as a valuable asset to every firm to improve performance. The current study looked at effect of work environment on performance of employees in Mbale City of Eastern Uganda. Specifically the study investigated how working conditions affect employee performance in Mbale City local government and how supervision affects employee performance in Mbale City local government. It also looked at the influence of employee's health and safety on their performance in Mbale City local government. The study used cross-sectional design to analyze data from the study area with the help of both qualitative and quantitative methods. The researcher collected data from 80 respondents in the study area who were selected using simple random and purpose sampling and questionnaires together with interview guide were used to collect data. The study found that organizations should be concerned worker’s safety should provide workers with better housing and office space. Also, workers should be provided with sufficient medical facilities and organizations should provide workers with transportation and they are in good condition. Also, workers should have good office structure and facilities and the office/working space should be adequate to keep work documents. The study recommended that employees should follow law full instructions from my superiors and should be supervised regularly in addition to reviewing performance regularly. Employees should submit reports on accomplished tasks to my supervisor, and their work should be closely monitored. Other results showed that employees should be provided with work protection gears and should be provided with safety tools at work. Organizations should trains its employees in health and work safety, sanitation facilities are provided and adequate safety precautionary measures should be provided by the organization.